Bladder Exposure to Gardnerella Activates Host Pathways Necessary for Escherichia coli Recurrent UTI - O’Brien, Valerie P.; Lewis, Amanda L.; Gilbert, Nicole M. (Frontiers in Cellular and Infection Microbiology, 2021)
Recurrent urinary tract infections (rUTI) are a costly clinical problem affecting millions of women worldwide each year. The majority of rUTI cases are caused by uropathogenic Escherichia coli (UPEC). Data from humans and mouse models indicate that some instances of rUTI are caused by UPEC emerging from latent reservoirs in the bladder. Women with vaginal dysbiosis, typically characterized by high levels of Gardnerella and other anaerobes, are at increased risk of UTI. Multiple studies have detected Gardnerella in urine collected by transurethral catheterization (to limit vaginal contamination), suggesting that some women experience routine urinary tract exposures. We recently reported that inoculation of Gardnerella into the bladder triggers rUTI from UPEC bladder reservoirs in a mouse model. Here we performed whole bladder RNA-seq to identify host pathways involved in Gardnerella-induced rUTI. We identified a variety host pathways differentially expressed in whole bladders following Gardnerella exposure, such as pathways involved in inflammation/immunity and epithelial turnover. At the gene level, we identified upregulation of Immediate Early (IE) genes, which are induced in various cell types shortly following stimuli like infection and inflammation. One such upregulated IE gene was the orphan nuclear receptor Nur77 (aka Nr4a1). Pilot experiments in Nur77-/- mice suggest that Nur77 is necessary for Gardnerella exposure to trigger rUTI from UPEC reservoirs. These findings demonstrate that bladder gene expression can be impacted by short-lived exposures to urogenital bacteria and warrant future examination of responses in distinct cell types, such as with single cell transcriptomic technologies. The biological validation studies in Nur77-/- mice lay the groundwork for future studies investigating Nur77 and the Immediate Early response in rUTI.